The Office of Women's Empowerment, Child Protection and Family Planning: Are they responsive? - Berutu, Jepriadi; Nashriyah, Nashriyah; Zamharira, Cut (Universitas Islam Negeri Ar-Raniry, 2023)
Protection is an absolute thing to do, especially for the children who are victims of sexual violence. The government must be responsive to take remedial action so that children who are victims of this violence can return to their normal environment. This study aims to determine the responsiveness of Subulussalam Women's Empowerment, Child Protection and Family Planning Service (the so called DP3AKB) in providing protection for children who experience sexual violence. The method used was qualitative with data consisting of primary and secondary data. Data were obtained through observation, interviews and documentation. The results of the study indicated that Women's Empowerment Agency for Child Protection and Family Planning Office in Subulussalam was quite responsive in providing protection for children who experience sexual violence, but the responsiveness has not been carried out optimally. This can be seen from a). the ability of the bureaucracy to recognize the needs of child victims of sexual violence is good, b) the ability to develop a priority agenda for protecting children against sexual violence is in accordance with what is needed by child victims of sexual violence, and c) the ability to develop programs to protect children from sexual violence in the form of safe houses. The obstacles DP3AKB experienced in carrying out their duties were the lack of information and budget limitations experienced by DP3AKB of Subulussalam.